The synthesis, characterization and properties of new organometallic polymers - Zeng, Renqiang (Department of Chemistry, 2017)
We have reviewed recent work on highly branched polymers called dendrimers. Two novel block copolymers consisting of organoruthenium dendritic wedges and linear polyethylene glycol blocks have been prepared. These new block copolymers have been characterized by IR, ¹H and ¹³C NMR, microanalysis, as well as size exclusion chromatography. The SEC results of some very large organoruthenium dendrimers are also discussed. The thermal properties of these block copolymers have been studied by differential scanning calorimetry and thermogravimetric analysis. The morphology of these block copolymers have been studied by transmission electron microscopy. We also describe a preliminary thin film study, resulting from the decomposition of some of the block copolymers. Two ruthenium and platinum complexes containing bulky dendritic phosphine ligands, cis-Pt(RDP)₂Cl₂ and trans,trans,trans-RuCl₂(CO)₂(RDP)₂, have been prepared. These new phosphine complexes have been characterized by IR, ¹H, ¹³C and ³¹P NMR, as well as elemental analysis. We also discuss the potential catalytic application of these dendritic phosphine metal complexes in the hydroformylation reaction.